Znajdź y 4n0n:
sin(x−y)−1 

= x+C
cos(x−y) 
6 kwi 19:33
4n0n: bump
7 kwi 19:48
Mariusz:
 x−y x−y 
2sin(

)cos(

)−1
 2 2 
 

 x−y x−y 
cos2(

)−sin2(

)
 2 2 
 
 x−y x−y 
2tg(

)cos2(

)−1
 2 2 
 

 x−y x−y 
cos2(

)−sin2(

)
 2 2 
 
 x−y x−y 
2tg(

)−(1+tg2(

))
 2 2 
 

 x−y 
1−tg2(

)
 2 
 
 x−y x−y 
−tg2(

)+2tg(

)−1
 2 2 
 

 x−y 
1−tg2(

)
 2 
 
 
 x−y 
(tg(

)−1)2
 2 
 

 
 x−y x−y 
(1−tan(

))(1+tg(

))
 2 2 
 
 x−y x−y 
(tg(

)−1)(1−tg(

))
 2 2 
 

 x−y x−y 
(1−tg(

))(1+tg(

))
 2 2 
 
 x−y 
tg(

)−1
 2 
 

 x−y 
1+tg(

)
 2 
 
 x−y π 
tg(


)= x + C
 2 4 
x−y π 


=arctg(x + C)
2 4 
x−y π 

=

+arctg(x + C)
2 4 
 π 
x−y =

+2arctg(x + C)
 2 
 π 
y = x −

− 2arctg(x + C)
 2 
12 kwi 07:38